The Use of Short Stories as a Media of Cultural Diplomacy in BIPA Learning at Phatnawitya School, Yala, Thailand - Farichah, Amilatul; Budiawan, R. Yusuf Sidiq; Ulfiyani, Siti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the use of Indonesian short stories as a medium of cultural diplomacy in learning Indonesian for Foreign Speakers (BIPA) at Phatnawitya School, Yala, Thailand. Although literary texts have long been used in BIPA learning, studies that specifically examine their role as an instrument of cultural diplomacy in the context of multicultural education are still limited. The purpose of this study is to describe the use of short stories as a means of cultural diplomacy in the BIPA learning process at Phatnawitya School. This study uses a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results of the study showed that short stories were effective in improving the language skills of foreign learners, including reading, writing, listening, and speaking skills. In addition, the use of short stories also encourages understanding and appreciation of Indonesian culture. The learners showed high enthusiasm and were able to express their ideas through the presentation of their work. Thus, short stories have proven to contribute positively to the development of language competence and become a means of conveying Indonesian cultural values subtly (soft diplomacy) in the realm of international education.